Structure and magnetic properties of diluted magnetic metal oxides based on Cu-doped CeO2 nanopowders. Issue 1 (January 2015) - Al-Agel, Faisal A.; Al-Arfaj, Esam; Al-Ghamdi, Ahmed A.; Stein, Barry D.; Losovyj, Yaroslav; Bronstein, Lyudmila M.; Shokr, F.S.; Mahmoud, Waleed E.
Abstract: The development of engineered nanostructures with precise morphology has gained significant attention due to new properties of these materials. Herein, we report a novel recipe to synthesize Ce1− x Cu x O nanostructures via a hexamethylene triperoxide diamine assisted solvothermal method. The influence of Cu ion concentration (0.01≤ x ≤0.10) on the structure and morphology of the CeO nanocrystals was examined. The X-ray photoelectron spectroscopy demonstrated that the copper atoms tend to be incorporated into the CeO crystal structure in the form of Cu 2+ . At the Cu ion concentration x =0.09, the Cu-doped CeO2 displayed a very high saturation magnetic moment of 1.58 μB /Co and coercivity of 154 G. The synthetic method designed in this work enhanced the ferromagnetic properties of the Ce1− x Cu x O nanostructures compared to the materials obtained by conventional techniques.